ELLIPSIS IN RUSSIAN SYNTAX AND ITS COMMUNICATIVE FUNCTIONS - Saidova Olima Botirovna (International Journal of Literature and Language Studies, 2026)
This article examines the phenomenon of ellipsis in modern Russian syntax from the perspective of its structural characteristics and communicative functions. Special attention is paid to the role of elliptical constructions in achieving linguistic economy, expressiveness, and communicative efficiency. The study analyzes different types of ellipsis in spoken and written discourse and highlights their pragmatic significance in communication. The research is based on examples from conversational speech, literary texts, and media discourse. The findings show that ellipsis is an essential linguistic mechanism that enhances communicative efficiency and reflects the principle of language economy.